HUBUNGAN ANTARA PENGETAHUAN DENGAN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA MAHASISWA UNIVERSITAS PANCA SAKTI BEKASI - Saputra, Hendriyatna Adi; Nugroho, Moh Taufan; Siahaan, Leroy Holman (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the relationship between taxpayers’ level of knowledge and their compliance in fulfilling tax obligations. The research serves as a study material and scientific reference, particularly for students of the Management Study Program, to better understand the importance of tax knowledge in improving taxpayer compliance. The method used is quantitative, with a survey approach utilizing a questionnaire as the data collection instrument. The number of respondents in this study was 10 taxpayers.Data analysis was carried out using IBM SPSS Statistics version 27. The validity and reliability tests indicated that all questionnaire items were valid and reliable for use in the study.The correlation test results showed a significant relationship between the knowledge variable(X) and compliance variable (Y) overall, with a total correlation value of r = 0.913 and a significance value (p) < 0.01, indicating a very strong and statistically significant relationship.From these results, it can be concluded that the higher the taxpayers’ level of knowledge, the higher their level of compliance in fulfilling their tax obligations.